PENGARUH BERBAGI PENGETAHUAN DAN DUKUNGAN ORGANISASI TERHADAP KEPUASAN KERJA : STUDI PADA SMPN DI KECAMATAN CAKUNG - Aruan, Yosie Anggriani Elisabeth; Sholikha, Sholikha; Wolor, Christian Wiradendi (Jurnal Pijar, 2023)
The purpose of this study is to analyze: (1) the effect of knowledge sharing on job satisfaction, (2) the effect of organizational support on job satisfaction, (3) the effect of knowledge sharing and organizational support on job satisfaction. The number of samples in this study was 125 teachers in SMPN in Cakung District. The sample technique is Non Probability Sampling and the data was collected using questionnaires. The analysis technique used is descriptive analysis. The results found that (1) knowledge sharing had a positive effect on teacher job satisfaction in SMPN in Cakung District, (2) organizational support had a positive effect on teacher job satisfaction in SMPN in Cakung District. (3) knowledge sharing and organizational support positively affect teacher job satisfaction in SMPN in Cakung sub-district by 34,2% and the remaining 65,8% is influenced by other variables.